Pengaruh Diskon dan Gratis Ongkir Terhadap Keputusan Pembelian Masyarakat Pada Aplikasi Shopee (Studi Masyarakat RT 19 Perumahan Mutiara Puri Harmoni) : The Effect of Discounts and Free Shipping on People's Purchase Decisions on the Shopee Application (RT 19 Community Study) Pertiara Puri Harmoni Housing) - Hening Mahaputri; Susanti Susanti (CV Warnak Johanna Nusantara, 2026)
This study aims to examine the extent to as which discounts and free shipping services shape the shopping patterns of Shopee app users, focusing on the residents of RT 19 in the Mutiara Puri Harmoni housing complex. A quantitative, correlational approach was applied, with primary data gathered from a survey distributed to 100 respondents. The analytical procedure covered instrument validity and reliability testing, multiple linear regression, t-tests and F-tests, along with the computation of the coefficient of determination, all processed through IBM SPSS Statistics version 27. Findings reveal that both discount and free-shipping variables contribute positively and significantly to purchasing decisions. When tested jointly, the two variables were likewise found to exert a significant effect, reflected in an F-value of 112.237 at a significance level below 0.001. The resulting coefficient of determination (R-squared) of 0.698 indicates that 69.8% of the variation in purchasing decisions can be attributed to the combined effect of discounts and free shipping, with the remaining portion explained by factors outside the scope of this study. Notably, the free-shipping variable was found to carry a stronger influence on Shopee purchasing decisions than the discount variable. Keywords: